Outpatient coordination reform improves the sustainability of China's Urban Employee Basic Medical Insurance Fund - Jingping Lin; Chengming Yan; Hanning Wang; Cong Xu; Weiqiang Fan (Frontiers Media S.A., 2024)
This study aims to examine the impact of outpatient coordination reform (OCR) on the sustainability of the Urban Employee Basic Medical Insurance (UEBMI) pooling fund. Using an employee medical insurance pooling fund model, we found that, without OCR, the fund will face current deficits by 2024 and cumulative deficits by 2033. However, with the "partial outpatient coordination reform," offering 50 or 75.6% reimbursement rates, the onset of cumulative deficits is delayed by 11 and 8 years, respectively. In contrast, implementing the "complete outpatient coordination reform" with 50 or 75.6% reimbursement rates ensures a positive cumulative balance until 2050. In conclusion, OCR not only strengthens the mutual assistance function of medical insurance but also ensures the sustainability of the insurance fund. Therefore, it is advisable to implement and refine these policies promptly to reduce the financial burden on the UEBMI pooling fund.